An optimised credit scorecard to enhance cut-off score determination - Nico Kritzinger; Gary W. van Vuuren (South African Journal of Economic and Management Sciences, 2018)
Background: Credit scoring is a statistical tool allowing banks to distinguish between good and bad clients. However, literature in the world of credit scoring is limited. In this article parametric and non-parametric statistical techniques that are used in credit scoring are reviewed.